2011
DOI: 10.1016/j.ajpath.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Human Renal Cell Carcinoma Induces a Dendritic Cell Subset That Uses T-Cell Crosstalk for Tumor-Permissive Milieu Alterations

Abstract: The mononuclear infiltrate in renal cell carcinoma (RCC) has been associated with the immunogenic nature of this tumor type and the clinical response rates achieved with immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 61 publications
9
65
0
3
Order By: Relevance
“…In kidney, DC-SIGN is a protein that labels activated myeloid DCs with high T cell stimulation capability. 20 By performing double immunostaining for DC-SIGN/BDCA-1 in kidney frozen samples, Woltman et al 8 confirmed the reliability of DC-SIGN as a marker of myeloid kidney DCs by showing that all DC-SIGN + cells expressed BDCA-1. In this report, we observed DC-SIGN staining in elongated cells with cytoplasmic protrusions that were mainly present in the interstitium.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In kidney, DC-SIGN is a protein that labels activated myeloid DCs with high T cell stimulation capability. 20 By performing double immunostaining for DC-SIGN/BDCA-1 in kidney frozen samples, Woltman et al 8 confirmed the reliability of DC-SIGN as a marker of myeloid kidney DCs by showing that all DC-SIGN + cells expressed BDCA-1. In this report, we observed DC-SIGN staining in elongated cells with cytoplasmic protrusions that were mainly present in the interstitium.…”
Section: Discussionmentioning
confidence: 91%
“…18,19 In kidney biopsies, DC-SIGN + cells stain with other known kidney DC markers (BDCA-1, 8 HLA-DR, 8 CD68, 7,8 and CX3CR1 10 ), show an activated but not fully mature DC phenotype, and are associated with high T cell stimulation capability. 20 Our knowledge of the role of kidney DCs in human allografts is limited to three studies 8,9,21 (Table 1). These studies have shown that compared with the pretransplant baseline, rejecting allografts display increased number of DCs, which are associated with inflammation, atrophy, and subsequent allograft dysfunction.…”
mentioning
confidence: 99%
“…Interestingly, these two types of DCs display different phenotypes and capacities of T-cell priming, presumably due to the distinctive microenvironments in which they develop. Isolated DCs display an immature phenotype (CD80 À , CD86 À , CD83 À , and HLA-DR À ) (Gigante et al, 2009;Giraldo et al, 2015), express tumor-promoting molecules (eg, TNF-α and MMP-9) (Figel et al, 2011), and induce a dysfunctional in vitro T-cell activation (Cabillic et al, 2006;Figel et al, 2011). On the other hand, DCs within immune aggregates exhibit a mature phenotype and express activation markers Middel, Brauneck, Meyer, & Radzun, 2010;Troy et al, 1998) (Fig.…”
Section: The Ccrcc Tumor Microenvironmentmentioning
confidence: 98%
“…CD14 is a specific monocyte/macrophage marker, although it can also be found on subsets of dendritic cells. 26 CD33 is expressed on non-terminally differentiated myeloid cells 27 and CD163 is linked to macrophage anti-inflammatory functions. [28][29][30] The cellular distribution of these myeloid cell populations in tumor epithelium and stroma is depicted in Table 2C.…”
Section: Infiltration Of Myeloid Cell Populationsmentioning
confidence: 99%
“…26 CD33 is expressed on non-terminally differentiated myeloid cells 27 and CD163 is linked to macrophage anti-inflammatory functions. [28][29][30] The cellular distribution of these myeloid cell populations in tumor epithelium and stroma is depicted in Table 2C. In general, tumors displayed a suppressive microenvironment as indicated by the high numbers of CD163-positive cells present.…”
Section: Infiltration Of Myeloid Cell Populationsmentioning
confidence: 99%